MIRERC 039/2025: POINT PREVALENCE SURVEY OF ANTIMICROBIAL USE AND HEALTHCARE-ASSOCIATED INFECTIONS THROUGH THE GLOBAL-PPS PROGRAM AT MERU TEACHING AND REFERRAL HOSPITAL - Joyster, Dr. Mungania; Dr. Divina Onchari, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Background: Antimicrobial resistance (AMR) is a growing public health crisis, especially in low-resource settings. High antimicrobial use is one of the major drivers of AMR at the hospital level, exacerbated by healthcare-associated infections (HAIs) that lead to increased morbidity, mortality, and healthcare costs. The Global-PPS program provides quantifiable measures to assess and compare the quantity and quality of antimicrobial prescribing, prevalence of healthcare-associated infections (HAI), and resistance. Objectives: This study aims to determine the prevalence and appropriateness of antimicrobial use, the prevalence of healthcare-associated infections, and the identification of targets to inform antimicrobial stewardship interventions. Methodology: A point prevalence study collecting data from patient records across all inpatient units at MeTRH. Antimicrobial use will be taken as any patient on any antimicrobial agent at 8.00 am on the day of data collection. Other parameters such as missed antimicrobial doses, indications, healthcare-associated infections, and use of susceptibility testing will also be assessed. Data Analysis: Data will be analyzed through the Global-PPS program, which will provide a report on all parameters and units. The data will be presented in proportions and figures. Expected outcomes: The report from this study will provide baseline data to help the hospital’s antimicrobial stewardship committee identify targets for antimicrobial stewardship and help change practice. Future iterations will allow comparison to assess the effectiveness of such interventions.